Memahami Konsep Kesempurnaan Tabiat dari Kelompok 144.000 dalam Hubungannya Dengan Pertentangan Besar dari Sudut Pandang Gereja Advent berdasarkan Wahyu 14:4-5 - Rumalag, David Calvin W.; Pardosi, Milton T. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The cosmic warfare that ensued between good and evil, led to great accusations against the reign of Christ and its Rule. Satan's resounding accusation is that God's Law is too onerous to be the rule for Human life, thus God's Rule does not provide and even infringes on the freedom of every Individual. By opposing the Law of God, Satan is openly opposing the Reign of God. The cosmic warfare between God and Satan causes Man to be involved in it. Proof of God's loving rule without infringing on each individual's freedom of choice had to be proven. The perfection of character is an issue that continues to be discussed among theologians. Given the corrupt condition of mankind, achieving perfection seems to be an impossible thing to achieve, but this message is what the 144,000 in Revelation 14:4-5 will have, where they are not defiled, there is no lie in their mouths and they are blameless. This is the main issue in this study.